Cellobiose fermentation by Saccharomyces cerevisiae: Comparative analysis of intra versus extracellular sugar hydrolysis. (December 2018) - Casa-Villegas, Mary; Polaina, Julio; Marín-Navarro, Julia
Graphical abstract: Highlights: Extra and intracellular cellobiose hydrolysis by Saccharomyces was analyzed. The bottleneck for efficient intracellular cellobiose fermentation is sugar intake. Ten sugar permeases from Trichoderma reesei were assayed in Saccharomyces. Only one assayed sugar permease had cellobiose transport activity in Saccharomyces . Extracellular cellobiose hydrolysis outperformed intracellular fermentation. Abstract: A prevalent procedure for the production of second generation bioethanol makes use of engineered yeast strains capable to hydrolyze cellobiose either in the cytosol or extracellularly. These two approaches have been compared in this study. For intracellular cellobiose hydrolysis, we initially tested three recombinant Saccharomyces cerevisiae strains that produced different cytosolic β-glucosidases and the cellodextrin transporter Po_CdtC from Penicillium oxalicum . The strain coexpressing Po_CdtC and the β-glucosidase from Neurospora crassa (NcBgl) showed the highest cellobiase activity but its growth in cellobiose was limited by sugar intake. A search of alternative cellobiose permeases was carried out among putative sugar transporters from Trichoderma reesei . Ten candidates were selected by sequence similarity with previously characterized fungal cellobiose permeases. Only one of them (Tr_StrC) was able to support yeast growth in cellobiose. Strains NcBgl/PoCdtC and NcBgl/TrStrC were compared to a yeast transformant (T500) that produced the extracellular β-glucosidase from Saccharomycopsis fibuligera, in terms of cellobiose fermentation. Extracellular hydrolysis resulted in faster cellobiose fermentation rates and higher ethanol yields. The strain producing extracellular β-glucosidase was also more efficient for simultaneous saccharification and fermentation of cellulose. The main targets to improve cellobiose fermentation through both strategies are discussed.